PENGARUH INTELEGENSI, MOTIVASI BELAJAR, DAN MINAT BELAJAR TERHADAP HASIL BELAJAR EKONOMI KELAS XI IPS DI SMA NEGERI KOTA MOJOKERTO - Sari, Jenitta Vaulina Puspita (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aimed to analyze the effect of intelligence, learning motivation, and learning interest, partially and simultaneously on learning outcomes of economics in grade XI Social Class SMA Negeri Kota Mojokerto. The sample was 184 students in grade XI social class. The study used a quantitative approach. Data were analyzed using multiple linear regression. The results of this study indicate that (1) there is significant effect between intelligence on learning outcomes of economics in grade XI Social Class SMA Negeri Kota Mojokerto; (2) there is significant effect between learning motivation on learning outcomes of economics in grade XI Social Class SMA Negeri Kota Mojokerto; (3) there is significant effect between learning interest on learning outcomes of economics in grade XI Social Class SMA Negeri Kota Mojokerto; and (4) there is simultaneous effect between intelligence, learning motivation, and learning interest on learning outcomes of economics in grade XI Social Class SMA Negeri Kota Mojokerto. Based on the results, it can be concluded that intelligence, learning motivation, and learning interest are factors that effectively effect on the learning outcomes of students, but the other factors that affect learning outcomes, such as physiological factors, psychological, family, school, and society should also be considered to achieve optimal learning outcomes of economics